Customized fault management system for low distribution automation system - Ahmed, Musse Mohamud; Soo, W. L. (2008)
This paper presents the development of a fault management system for distribution automation system (DAS) for operating and controlling low voltage (LV) down stream of 415/240V. The fault management system is referred as the fault detection, fault location, fault isolation, supply restoration and manual control. The system is equipped with automated equipment to detect earth fault and overcurrent conditions. An embedded Ethernet controller is used as remote terminal unit (RTU) to act as converter for human machine interface (HMI)and to interact with the digital input and output modules. Supervisory Control and Data Acquisition (SCADA) is integrated with RTU for automatic operating and controlling the distribution system. The laboratory results are compared with the simulation results to make the final conclusion of the algorithm function properly.